Taxonomic novelties in Jacquemontia Choisy (Convolvulaceae) from Southeastern Brazil - Pastore, Mayara; Simão-Bianchini, Rosangela (Phytotaxa, 2015)
Two additional species are recognised in Jacquemontia. The new combination Jacquemontia frankeana is proposed, based on Convolvulus frankeanus, since this species is clearly referable to Jacquemontia rather than Convolvulus based on its stigma morphology and possession of stellate hairs. It is distinguished from closely related species of Jacquemontia by the glabrescent leaves, the stellate adpressed hairs with 4–5-rays, and the two outer sepals being smaller than the inner. Jacquemontia glabrescens is also recognized at specific rank, based on Jacquemontia grandiflora var. glabrescens. It is distinguished from the morphologically similar J. ferruginea and J. cataractae by a combination of glabrescent leaves, bigger flowers, rhombic to ovate outer sepals and glabrous to glabrescent. Synonymy of these taxa and typification are also addressed.